Pengaruh Brand Ambassador terhadap Perilaku Loyalitas Pelanggan pada Pengguna Shopee: (Studi Kasus Pada Vidi Aldiano sebagai Brand Ambassador Shoppe Mall) - Syepi Hidayat; Novrian Maulana (AKUNTANSI 45, 2024)
This study aims to examine the impact of brand ambassador, specifically Vidi Aldiano, on customer loyalty behavior among Shopee users. Utilizing a quantitative approach, data was collected and analyzed using statistical methods, including T-test and coefficient of determination (R²). The analysis results indicate that the brand ambassador has a positive and significant influence on customer loyalty, with a t-value (2.995) exceeding the t-table value (1.987) and an R² value of 0.562, indicating that 56.2% of the variation in customer loyalty can be explained by the presence of the brand ambassador. These findings support the hypothesis that the strategy of employing a brand ambassador is effective in enhancing loyalty in the e-commerce industry. However, this study also has limitations, such as focusing on a single platform and a limited sample size, necessitating caution in generalizing the results. Future research is suggested to include comparisons across different platforms and consider other factors that may influence customer loyalty, as well as conduct longitudinal studies to explore how the impact of the brand ambassador evolves over time.